2022
DOI: 10.1136/neurintsurg-2021-018505
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for isolated posterior cerebral artery occlusion stroke in the MR CLEAN registry

Abstract: BackgroundEndovascular treatment (EVT) is standard of care in anterior circulation large vessel occlusions. In posterior circulation occlusions, data on EVT in isolated posterior cerebral artery (PCA) occlusions are limited, although PCA occlusions can cause severe neurological deficit.ObjectiveTo describe in a prospective study the clinical manifestations, outcomes, and safety of EVT in isolated PCA occlusions.MethodsWe used data (2014–2017) from the MR CLEAN Registry, a nationwide, prospective cohort of EVT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Twelve studies were included in the analysis [5, 12–16, 18, 19, 21, 25, 26, 29]. The search strategy is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies were included in the analysis [5, 12–16, 18, 19, 21, 25, 26, 29]. The search strategy is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EVT is increasingly used to treat patients with isolated occlusions of the PCA. Several recent studies demonstrated the feasibility and safety of EVT in these patients [5,[12][13][14][15][16][17][18][19][20][21]. However, randomized clinical trials demonstrating the efficacy of EVT in the treatment of isolated PCA occlusions are lacking.…”
Section: Although Clinical Symptoms Of Pca Infarcts May Results In a Lowmentioning
confidence: 99%
See 3 more Smart Citations